Inflammatory demyelinating polyneuropathy with nephrotic syndrome: Report of a case and review of the literature. Issue 1 (3rd April 2013) - Tateyama, Maki; Nakashima, Ichiro; Suzuki, Naoki; Kanaoka‐Suzuki, Chihiro; Takano, Rina; Sato, Hiroshi; Kusunoki, Susumu; Fujihara, Kazuo; Itoyama, Yasuto; Aoki, Masashi
Abstract An association between the acute or chronic form of inflammatory demyelinating polyneuropathy (IDP) and nephrotic syndrome has occasionally been reported. However, the clinical pictures in IDP of these cases have attracted little attention to date. In the present report, we describe a 50‐year‐old man with IDP who developed quadriplegia with respiratory impairment followed by a remitting and relapsing course for several months with complete recovery, in which nephrotic syndrome appeared at the nadir and subsided in parallel with the neurological improvement. We also searched for the English‐language literature from 1946 to 2012 April and found 32 cases of Guillain–Barré syndrome or chronic inflammatory demyelinating polyneuropathy with nephrotic syndrome. We analyzed the 33 cases including the present case, and found such features as: (i) male preponderance (84.8%); (ii) motor dominant impairments with favorable final outcomes; and (iii) proteinuria occurring simultaneously with neurological symptoms and ameliorating along with neurological improvement in the majority of the cases. Available data of nerve conduction studies consistently showed demyelinating neuropathy. These findings suggest that IDP with nephrotic syndrome might be a distinctive clinical entity possibly caused by immune reactions to antigen(s) shared by peripheral nerves and the glomerulus. As nephrotic syndrome is asymptomatic or transient in some cases, IDP with nephrotic syndrome might be more prevalent than we think.